(untitled) (Conference on English Language Teaching, 2023)
English language policy plays a significant role in enhancing the communication skills of the students. This descriptive-qualitative research was designed to explore the narratives of language learners regarding the essentiality of speaking English policy inside the classroom in which the ten (10) selected participants were chosen purposely as subjects to achieve the intended purpose of the study and the data were gathered through the use of in-depth interview in an online platform for virtual meetings. Their responses were thematically analyzed using Colaizzi’s method. The major findings revealed that speaking English language policy inside the classroom impacted the learner’s language learning and development, producing more proficient learners and evoking positive and negative circumstances. These findings indicated to be advantageous to the learners, like boosting their self-esteem in effectively utilizing the universal language that help enhances their intellectual capacity and hones the delivery of language for efficient communication. It reveals the pivotal role of speaking English policy to the language learner. Therefore, the researchers’ implication is the implementation of speaking English language policy inside the classroom to develop students’ fluency in uttering the language in daily interaction inside the learning environment, wherein this would improve students’ performances in demonstrating their speaking abilities.